Artificial Intelligence (AI) and its Application in Agriculture - Vijayakumar, S.; Kumar, R. Mahender; Choudhary, Anil Kumar; Deiveegan, M.; Tuti, Mangal Deep; Sreedevi, B.; Sundaram, R. M. (Chronicle of Bioresource Management, 2023)
Artificial intelligence (AI) holds the promise of driving an agricultural revolution at a time when we must produce more food using fewer resources and has begun to play a significant role. The main idea behind AI is to create technology that works similarly to the human brain. With the help of AI, it is possible to gather vast amounts of data from government and public websites, analyse it, and give farmers answer to many complex issues, as well as a smarter way of managing inputs by accounting all the variabilities within the field, resulting in higher yield. AI can also gather market trends, annual production, and customer needs, which will help the farmers to maximise agricultural returns through the use of inputs more efficiently. The automated irrigation system will reduce the manpower and time consumption in the process of irrigation. It also helps in significantly conserving water.